Treatment options for the overactive bladder syndrome. Issue 6 (November 2005) - Hashim, Hashim; Abrams, Paul
Urgency is the cornerstone symptom of overactive bladder (OAB) syndrome. It affects millions of people worldwide and has considerable effects on society. Most previous studies concentrated on urinary incontinence and it wasn''t until 2002, when the new definition of OAB was published, that interest in this condition began to increase. Unfortunately, the cause of OAB is not clearly established, thus all available treatments are aimed at alleviating symptoms rather than cure. Management is based on making an accurate diagnosis by excluding other pathologies and treating the symptoms conservatively and/or pharmacologically. Treatments are based on the assumption that OAB is due to involuntary detrusor contractions typical of detrusor overactivity. Antimuscarinic agents form the mainstay of medical therapy. There have been many recent developments in antimuscarinic drug therapy for OAB, which have gained more interest, particularly with the introduction of the term ''bladder selectivity'', and it is hoped that these newer agents will provide a wider variety of drugs that could help in the management of OAB. Should medical treatment fail and symptoms become unbearable, surgical treatment is the last resort. However, recently neuromodulation and possibly botulinum toxin have attempted to bridge the gap between oral pharmacologic and operative treatment.